2001
DOI: 10.1046/j.1365-2346.2001.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane and nitrous oxide anaesthesia suppresses heart rate variabilities during deliberate hypotension

Abstract: Sevoflurane in nitrous oxide and oxygen anaesthesia reduces sympathetic autonomic activity considerably, and the expected increases caused by hypotensive agents that occur in awake volunteers were not seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…We also observed an increase in heart rate with sevoflurane and a correlation between the decrease in high frequency power and heart rate variability. This agrees with studies done in patients [15]. Our data indicate that heart rate entropy and cardiac vagal activity decrease in a similar way during sevoflurane anesthesia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also observed an increase in heart rate with sevoflurane and a correlation between the decrease in high frequency power and heart rate variability. This agrees with studies done in patients [15]. Our data indicate that heart rate entropy and cardiac vagal activity decrease in a similar way during sevoflurane anesthesia.…”
Section: Discussionsupporting
confidence: 93%
“…It is unclear why there is a discrepancy between the results of Kanaya et al [5] that sevoflurane did not decrease high frequency activity and heart rate entropy while others found the opposite [11,15]. This may be related to sevoflurane dose.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…None of them was considered to have a low risk of bias. The best current evidence showed that the heart rate may be increased or may remain stable during deliberate hypotension, depending on the drug used to induce hypotension 55,56, 66,69,79,91,154 . Similarly, the cardiac output may or may not change depending on the anaesthetic technique used.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies showed an increase in heart rate during nitroprusside-induced hypotension 55,56,66 , one study showed the same effect during nicardipineinduced hypotension 91 and one study showed the same effect during nitroglycerin-induced hypotension 55 . Four studies demonstrated no significant change in heart rate during hypotension induced by nicardipine, nitroglycerin or alprostadil 154 It was demonstrated that the oxygen tension of arterial blood was decreased during hypotensive anaesthesia using nitroprusside 55,56 , labetalol 56 , prostaglandin E1 69 and nitroglycerin 55 . In one study, 18 out of 47 patients receiving nitroprussideRisks and benefits of deliberate hypotension in anaesthesia: a systematic review 693 1999 197 No significant differences between markedly hypotensive group (MAP at 45-55 mmHg) and less hypotensive group (MAP 55-70 mmHg) in the incidence of early or long-term cognitive dysfunction induced hypotensive anaesthesia showed electrocardiographic (ECG) changes which suggested ischaemia, but there was no clinical evidence of myocardial ischaemia.…”
Section: Cardiovascular Effects Of Hypotensive Anaesthesiamentioning
confidence: 98%